8 - La politique de la culture de maïs et de riz en campagne sèche : atouts et achoppements au Burkina Faso (2001–2016) - Zara Dao (Afrika Zamani, 2022)
Facing climatic adverse, Burkina Faso has developed irrigation as an alternative to intensify productivity and fight against climate change. Initially practiced in the rainy season, irrigation has been initiated in the dry season in order to increase cereal availability mainly of maize and rice. Based on irrigation policy and scientific and technological research as well, the practice of growing off- season crops offers many advantages such as better productivity and help fight against food crises. However, many obstacles, such as problems related to water and land tenure, impede the extension of farming in the dry season.